A rare case of mucinous cystedenoma in adoloscence - S., Shreevidya Bhat Y.; Tabassum, Neha; Anjum, Mehvish; D., Nivedita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Mucinous cystadenomas are one of the rarely found benign ovarian neoplasms seen in adolescents. They are commonly known for their massive size causing compressive effects ranging from pressure, pain, bloating, and urinary symptoms. As time passes by, these adnexal masses can lead to severe and fatal complications, such as ovarian torsion or haemorrhage. Accidental findings of these tumours are common as many of these patients are usually asymptomatic. Pelvic examinations and imaging studies can be used to further diagnose symptomatic patients and aid physicians in developing an appropriate course of treatment. A case of 18-year-old unmarried nulligravida presented with abdominal distension and mass per abdomen for the past 4 months, clinical examination revealed a mass of 32-34 weeks size, cystic in consistency, lower mass was not palpable, ultrasonography and magnetic resonance imaging (MRI) of abdomen and pelvis showed a large abdominopelvic multiloculated thin-walled lesion of size 17×21×30 with thin walled septations with enhancing intensity likely arising from the right adnexa. Mucinous cystadenoma patient was operated, staging laparotomy was done showed a huge large right ovarian cyst 26×15×9 cm, with no abnormalities noted in the uterus, appendix and left ovary. The histopathology report showed as mucinous cystadenoma. The patient was surgically managed by exploratory laparotomy with right ovarian salpingoophorectomy was done, patient was discharged in stable condition and advised follow-up in gynaecology OPD. Incidence of mucinous cystadenoma is very rare in adolescents. Here we report a case of mucinous cystadenoma, detailing the clinical presentation, diagnosis, pathologic review, imaging findings and management.